Judicial Response to the Doctrine of Specific Performance in Nepal - Kalika, Satya Narayan (Management Dynamics, 2020)
Specific Performance is one of the equitable remedies available to the victim of breach of contract awarded by a judicial decision in cases where damages are not adequate. This paper aims to highlight the legal principles and provisions of specific performance; Nepalese laws in that arena; and most specifically the judicial response to the doctrine whereby several case laws where the order of specific performance was granted or refused by the Supreme Court of Nepal have been examined. This doctrinal study has adopted exploratory descriptive and analytical method. The analysis is based on primary data drawn from the statute and major judicial decisions, and some secondary data drawn from articles, books and treatises on the issue. The nascent Muluki Civil Code, 2074 has also provided various remedies available to the victim party of breach of contract like its predecessor legislation, i.e. the erstwhile Contract Act, 2056. This paper thrives to explore the principle of specific performance of contract and to discuss the judicial responses to the doctrine of specific performance of contract in Nepal.